2017
DOI: 10.1002/acs.2802
|View full text |Cite
|
Sign up to set email alerts
|

A framework of iterative learning control under random data dropouts: Mean square and almost sure convergence

Abstract: This paper addresses the iterative learning control problem under random data dropout environments. The recent progress on iterative learning control in the presence of data dropouts is first reviewed from 3 aspects, namely, data dropout model, data dropout position, and convergence meaning. A general framework is then proposed for the convergence analysis of all 3 kinds of data dropout models, namely, the stochastic sequence model, the Bernoulli variable model, and the Markov chain model. Both mean square and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…In [28], authors indicated there are two kinds of methods to guarantee the convergence of ILC systems with data dropouts: Kalman filtering-based method and data compensation method. As to data compensation, this approach can be further divided into time domain compensation and iteration domain compensation.…”
Section: Convergence Speed Analysis Of the System With Successivmentioning
confidence: 99%
See 1 more Smart Citation
“…In [28], authors indicated there are two kinds of methods to guarantee the convergence of ILC systems with data dropouts: Kalman filtering-based method and data compensation method. As to data compensation, this approach can be further divided into time domain compensation and iteration domain compensation.…”
Section: Convergence Speed Analysis Of the System With Successivmentioning
confidence: 99%
“…Specifically, a P-type control update algorithm was proposed in [26] for the SISO affine nonlinear system with random output data losses and unknown control direction, and a simple P-type update law was used in [27] for both linear and nonlinear cases based on stochastic approximation. In [28], authors first reviewed the recent progress on the networked ILC systems with data dropouts from the perspective of data dropout model, data dropout position and convergence meaning, respectively. After that, a general framework was proposed for the convergence analysis of three different data dropout models, namely, the stochastic sequence model, the Bernoulli variable model and the Markov chain model.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the random variable k ðtÞ is multiplicative to the original signals. The ILC for systems with random data dropouts has been a hot topic in the past few years [60][61][62][63][64][65][66].…”
Section: Examples Of Multiplicative Randomnessmentioning
confidence: 99%
“…Various techniques have been provided from different perspectives. A systematic design and analysis framework for three data dropout models was reported in [65] based on the stochastic approximation techniques. For the other examples, systematic frameworks are still open.…”
Section: Possible Future Directionsmentioning
confidence: 99%
“…Shen and Wang proposed a P-type control update algorithm in [20] for a SISO affine nonlinear system with random measurement data losses and unknown control direction, and proposed a simple P-type update law for both linear and nonlinear cases based on stochastic approximation [21]. Shen and Xu [22] first reviewed the recent progress on networked ILC systems in the presence of data dropouts. After that, a general framework was proposed for the convergence analysis of three different data dropout models.…”
Section: Introductionmentioning
confidence: 99%